Analysis of Payment Transaction Systems Through QRIS: Regulations and Their Role in Realizing a Digital-Based National Economy - Farhan Ammar Lutfiansyah; Batara Wahyu Putera; Giftian Fajri Rustyono; Arlangga Surya Renata; Muhammad Hafiizh Nurhuda; Nanda Dwi Purnama; Sugeng Wibowo (Universitas Muhammadiyah Surakarta, 2023)
In this modern era, digital-based transaction systems can’t be separated from people's lives. The characteristics of digital-based financial transactions are practical, fast and efficient in consequence they can be able to facilitate the needs of the public in implementing payment transaction activities. In order to realize this, preparation is needed by considering various aspects such as regulations, facilities and infrastructure. The government through Bank Indonesia has responded by issuing QRIS as a QR code based payment. Bank Indonesia is also required to set regulations and prepare everything related to digitalization of the financial economy in Indonesia thus it can realize digital-based financial economic inclusion. Therefore, in writing this article the researchers tried to analyze and examine regulations and the role of QRIS in realizing a digital-based economy and creating an inclusive financial ecosystem.